External Fixation for Fracture Stabilization of the Sacrum in 15 Dogs - Flores, Jose Antonio; Rovesti, Gian Luca; Rodriguez-Quiros, Jesus (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the feasibility, complications, and outcomes of external fixation (EF) for the treatment of sacral fractures in dogs, either as a primary fixation system or a complementary technique. Fifteen dogs with sacral fractures were surgically treated using different EF configurations, either as primary or secondary stabilization. The results were evaluated for the extent of fracture reduction, stability during treatment, complications, and bone healing. In most cases, the outcomes were excellent in terms of bone healing, neurological condition, and pain assessment. The mean bone healing time was 9.45 ± 5.66 weeks. One patient (6.66%) presented a complication due to the technique. In conclusion, the use of EF should be considered for the stabilization of sacral fractures because of its minimal invasiveness, stability, and ease of application.